Generated topology on infinite sets by ultrafilters - Alireza Bagheri Salec (Sahand Communications in Mathematical Analysis, 2017)
Let $X$ be an infinite set, equipped with a topology $tau$. In this paper we studied the relationship between $tau$, and ultrafilters on $X$. We can discovered, among other thing, some relations of the Robinson's compactness theorem, continuity and the separation axioms. It is important also, aspects of communication between mathematical concepts.